Pengaruh Model Pembelajaran Pbl Berbantu Question Card Terhadap Kemampuan Berpikir Kritis Matematis Siswa Smp - Ratnawati, Dewi; Handayani, Isnaini; Hadi, Windia (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
This research aims to find out the influence used Problem Based Learning model assisted by Question Card toward students mathematic critical thinking skill in junior high school. This research was quantitative by using Quasi Experimental with the nonequivalent posttest-only control group design. The technique was purposive sampling method. The instrument of this method was six items, then validity test, reliability test, level of difficulty, and discrimination power. Normality and homogeneity test were used as requirement test and got the data was normal distribution and the two-group homogenous. The hypothesis test used t-test got the result 2,970 made Ho rejected with 5% significance level with effect size was 0,656 or 66% that moderate classified. Based on the result of this research, it can be concluded that there is an influence of problem-based learning model assisted by question card toward mathematic critical thinking skill with moderate criteria.